Dielectric Properties Of Mixing Palm Oil With Soybean Oil As A Potential Insulating Fluid In Transformer - Azmi, Kiasatina (2013)
Transformer is one of the most important equipments in electrical power system. Nearly all high voltage transformers are filled with oil to act as cooling medium and insulator. Generally, petroleum-based mineral oil is used as transformer oil. However, due to environmental concern and life-cycle of mineral oil, renewable resource such as vegetable oil is chosen as the best option to replace this mineral oil. Past researches have shown that palm oil has equivalent dielectric properties to substitute the mineral oil as liquid dielectric in electrical power transformer. However the kinematic viscosity does not fulfill the IEC 60296 standard requirements and need to be improved. One of the ways is by mixing the palm oil with soybean oil. So far, there are no reported studies on dielectric properties of palm oil and soybean oil mixture. Thus, in this project, the investigation on dielectric properties of RBDPO/RBDSO and RBDP Olein/FR3 mixtures was carried out. The ratios of soybean oil based products (RBDSO and FR3) in the palm oil (RBDPO and RBDP Olein) mixtures were limited to 50%. The dielectric properties of the oil mixture which are dielectric strength, dissipation factor (tan ), relative permittivity (dielectric constant), kinematic viscosity, water content and chemical composition analysis have been determined. The effect of mixing ratio and temperature variances of the oil mixtures to its dielectric properties has been investigated. The dielectric properties of RBDPO/RBDSO and RBDP Olein/FR3 also have been compared with mineral oil.